Laparoscopic Surgery of Gastroesophageal Reflux in Children - Dias, Ana (2013)
Introduction: Gastroeshophageal reflux is a common but usually innocuous condition in children. However, in the presence of Gastroeshophageal reflux disease, the surgical treatment (open or laparoscopic) may be indicated. This study aimed to evaluate the feasibility, effectiveness and safety of laparoscopic antireflux surgery (Nissen fundoplication) with emphasis in infants.Material and Methods: Children with gastroeshophageal reflux proposed for laparoscopic antireflux surgery between January 2006 and December 2012 in a pediatric surgery department of a university hospital were studied. A descriptive and comparative analysis was conducted with regard to age (group I: <1 year, group II: 1-3 years, group III: > 3 years) and presence of comorbidities. Demographics, symptoms, comorbidities, operative indications, perioperative and postoperative outcome were assessed. The statistical significance level was set at 5%.Results: 55 children were proposed for surgery: 12 of group I, 15 group of II and 28 of group III. 50.9% had comorbidities (21 central nervous system disease and 7 esophageal atresia). In 52 (94.5%) cases, antireflux surgery was performed by laparoscopy. The procedure lasted 167 ± 42 minutes, with no significant differences according to age groups, although higher in those with central nervous system disease. With a follow-up of 35.5 ± 23.9 months, the following complications occurred: gas-bloat syndrome, dumping or dysphagia in 8 cases (15.7%) and paraesophageal hernia in 2 cases (3.9%), with no significant differences between groups; there was clinical recurrence with reoperation in 2 cases.Conclusion: Laparoscopic Nissen fundoplication is a feasible and effective procedure, with minimal morbidity, including in infancy.